Refugee protection and the role of law : conflicting identities - Kneebone, Susan; Stevens, Dallal; Baldassar, Loretta, 1965- (Abingdon, Oxon : Routledge, 2014)
'Sixty years on from the signing of the Refugee Convention, forced migration and refugee movements continue to raise global concerns for hosting states and regions, for countries of origin, for humanitarian organisations on the ground, and, of course, for the refugee. This edited volume is framed around two themes which go to the core of contemporary'refugeehood' : protection and identity. It analyses how the issue of refugee identity is shaped by and responds to the legal regime of refugee protection in contemporary times. The book investigates the premise that there is a narrowing of protection space in many countries and many highly visible incidents of refoulement. It argues that'Protection', which is a core focus of the Refugee Convention, appears to be under threat, as there are many gaps and inconsistencies in practice. Contributors to the volume, who include Erika Feller, Elspeth Guild, Helene Lambert and Roger Zetter, look at the relevant issues from the perspective of a number of different disciplines including law, politics, sociology, and anthropology. The chapters examine the link between identity and protection as a basis for understanding how the Refugee Convention has been and is being applied in policy and practice. The situation in a number of jurisdictions and regions in Europe, North America, South East Asia, Africa and the Middle East is explored in order to ask the question does jurisprudence under the Refugee Convention need better coordination and how successful is oversight of the Convention?'--
Conflicting Identities, Protection and the Role of Law / Susan Kneebone, Loretta Baldassar and Dallal Stevens -- Creating Identities, Diminishing Protection and the Securitisation of Asylum in Europe / Roger Zetter -- Rights and the Re-identified Refugee : An Analysis of Recent Shifts in Canadian Law / Donald Galloway -- The Refugee Convention at 60 : Still Fit for Its Purpose? : Protection Tools for Protection Needs / Erika Feller -- Shifting Conceptions of Refugee Identity and Protection : European and Middle Eastern Approaches / Dallal Stevens -- Refugees as Objects of Surrogate Protection : Shifting Identities / Susan Kneebone -- Identifying Asylum Seekers as Potential Refugees : Transfers and'Acquired Rights' under the Refugee Convention / Maria O'Sullivan -- Conflicting Identities and Securitisation in Refugee Law : Lessons from the EU / Elspeth Guild -- Survival Migration : Conflicting Refugee Identities in Africa / Alexander Betts -- Transnational Law and Refugee Identity : The Worldwide Effect of European Norms / Helene Lambert -- Ambivalent Policies, Uncertain Identities : Asylum-Seeking Families in Sweden / Ulla Bjornberg -- Better than our fears? : Refugees in Italy between Rhetorics of Exclusion and Local Projects of Inclusion / Maurizo Ambrosini -- Moving beyond Protection Space : Developing a Law of Asylum in South East Asia / Martin Jones -- Law, identity and protection : Concluding Reflections / Dallal Stevens, Loretta Baldassar, Susan Kneebone and Loretta Baldassar.
Includes bibliographical references (pages 286-309) and index.
Keywords: Convention Relating to the Status of Refugees -- (1951 July 28); Refugees -- Legal status, laws, etc